Ultrafast construction of 3D ultrathin NiCo-LDH@Cu heteronanosheet array by plasma magnetron sputtering for non-enzymatic glucose sensing in beverage and human serum. (1st November 2022) - Tang, Xin; Zhang, Yu; Wu, Jiaying; He, Zhiyuan; Xing, Yun; Yang, Jie; Zou, Zhirong; Huang, Ke; Yu, Huimin; Xiong, Xiaoli
Highlights: Ultra-thin NiCo-LDH@Cu nanosheet array(NSA) in-situ growth on carbon cloth (CC). NiCo-LDH@Cu NSA/CC acts an efficient catalyst electrode for glucose oxidation. NiCo-LDH@Cu NSA/CC shows high sensing performance for glucose detection. NiCo-LDH@Cu NSA/CC operates efficiently in beverage and human serum samples. Abstract: In this work, a 3D ultra-thin NiCo-LDH nanosheet array coated Cu nanoparticles on carbon cloth (NiCo-LDH@Cu NSA/CC) was ultrafast synthesized by plasma magnetron sputtering for the first time. This method has low toxicity and is easy to operate. As a durable and efficient 3D heteronanoarray electrocatalyst for glucose detection, NiCo-LDH@Cu NSA/CC has higher stable conductivity and faster electron transport rate than NiCo-LDH NSA/CC and Cu nanoparticles, which work through synergistic effect to form a high-performance sensing platform. The NiCo-LDH@Cu NSA/CC heteronanosheet structure has good electrocatalytic performance for glucose oxidation, with the sensitivity of the two linear ranges (0.001–1 mmol L −1 and 1–6 mmol L −1 ) being 9710 μA L mmol −1 cm −2 and 4870 μA L mmol −1 cm −2, respectively, and the detection limit (LOD) is 157 nmol L −1 (S/N = 3). The sensor has been successfully applied to detect glucose in beverages and serum.